Hedgehog, Chamomile, and Multipetal Polymeric Structures on the Nanoparticle Surface: Computer Modelling - Zakhar R. Saraev; Alexei A. Lazutin; Valentina V. Vasilevskaya (Molecules, 2022)
A single spherical nanoparticle coated with a densely grafted layer of an amphiphilic homopolymer with identical A-graft-B monomer units was studied by means of coarse-grained molecular dynamics. In solvent, selectively poor for mainchain and good for pendant groups; the grafted macromolecules self-assemble into different structures to form a complex pattern on the nanoparticle surface. We distinguish hedgehog, multipetalar, chamomile, and densely structured shells and outline the area of their stability using visual analysis and calculate aggregation numbers and specially introduced order parameters, including the branching coefficient and relative orientation of monomer units. For the first time, the branching effect of splitting aggregates along with the distance to the grafting surface and preferred orientation of the monomer units with rearrangements of the dense compacted shell was described. The results explain the experimental data, are consistent with the analytical theory, and are the basis for the design of stimulus-sensitive matrix-free composite materials.